Development and Validation of the Isakson Survey of Academic Reading Attitudes (ISARA). Issue 2 (5th July 2016) - Isakson, Richard L.; Isakson, Marné B.; Plummer, Kenneth J.; Chapman, Sara B.
Abstract : The literature reveals that no adequate instrument exists to measure college students' attitudes toward academic reading even though such attitudes are crucial for reading compliance and learning from text. To remedy this, the authors created and refined an attitude survey, administering it to 855 university students across four iterations. The resulting 20-item instrument measures academic reading attitudes on three subscales: (1) students' perceived academic reading behaviors, (2) their expectations for success with academic reading tasks, and (3) the value they place on academic reading. Factor analyses demonstrated acceptable fit using this three-factor structure. Reliability coefficients estimating internal consistency ranged from .800 to .890. Correlations among the three-factor subscales varied from .365 to .675. Implications of the survey for research and attitude assessment are discussed.